Design and noise analysis of a sigma-delta capacitive micromachined accelerometer - 刘云涛 刘晓为 陈伟平 吴群 (Journal of semiconductors, 2010)
A single-loop fourth-order sigma-delta（ΣΔ） interface circuit for a closed-loop micromachined accelerometer is presented.Two additional electronic integrators are cascaded with the micromachined sensing element to form a fourth-order loop filter.The three main noise sources affecting the overall system resolution of aΣΔaccelerometer, mechanical noise,electronic noise and quantization noise,are analyzed in detail.Accurate mathematical formulas for electronic and quantization noise are established.The ASIC is fabricated in a 0.5μm two-metal two-poly n-well CMOS process.The test results indicate that the mechanical noise and electronic noise are 1μg/（Hz）~（1/2） and 8μV/（Hz）~（1/2） respectively,and the theoretical models of electronic and quantization noise agree well with the test and simulation results.